Bimodal Heterogeneous Functionality in Redox‐Active Conjugated Microporous Polymer toward Electrocatalytic Oxygen Reduction and Photocatalytic Hydrogen Evolution. Issue 17 (6th March 2020) - Singh, Ashish; Verma, Parul; Samanta, Debabrata; Singh, Tarandeep; Maji, Tapas Kumar
Abstract: The designing and development of heterogeneous catalysts for conversion of renewable energy to chemical energies by electrochemical as well as photochemical processes is at the forefront of energy research. In this work, two new donor–acceptor‐based redox‐active conjugated microporous polymers (CMPs) (TAPA‐OPE‐mix and TAPA‐OPE‐gly) are synthesized through Schiff base condensation reaction using a microwave synthesizer. Notably, the asymmetric and symmetric bola‐amphiphilic nature of the OPE struts results in distinct nanostructuring and morphologies in the CMPs. Interestingly, both CMPs show impressive heterogeneous catalytic activity toward electrochemical O2 reduction and photocatalytic H2 evolution reactions, and therefore, act as bimodal electro‐ and photocatalytic porous organic materials. Furthermore, the redox‐active property of the CMPs is exploited for in situ generation and stabilization of platinum nanoparticles (Pt), and these Pt@CMPs exhibit significantly enhanced photocatalytic activity. Abstract : Bifunctional catalyst : Bimodal functionality toward electrochemical O2 reduction and photochemical H2 evolution of donor–acceptor‐based redox‐active conjugated microporous polymers (CMPs) is explored. Tuning of the side‐chain substitutions on oligo‐( p ‐phenyleneethynylene bola‐amphiphilic struts shows distinct nanostructuring in CMPs, which has a high impact on catalytic performances.